The Mediating Role of Personality Traits in the Relationship between Parenting Style and Callous-Unemotional Traits - Fatemeh Kargar; Ghasem Norouzi; Amir Ghamarani (پژوهش‌های کاربردی روانشناختی, 2025)
The aim of the present study was to examine the mediating role of personality traits in the relationship between parenting style and callous-unemotional traits. The research method was basic in its approach to data acquisition, which included correlational and structural equation analysis. The male pupils of the first secondary school in Qom in 2021 comprised the statistical population of the research. Using the convenient technique, 451 individuals who were diagnosed with conduct disorder using the Children Symptom Inventory (SCI-4) and were willing to participate were selected from this community. Data were collected using the parenting style inventory (PSI), Inventory callous-unemotional (ICU), and Neuroticism-Extraversion-Openness Five-Factor Inventory (NEO-FFI). Pearson correlation and structural equation modeling were performed to analyze the data using SPSS version 21 and AMOS version 24. The results indicated that the direct effect of authoritarian and permissive parenting on Callous-Unemotional traits was both significant and positive. Based on the findings of the present study, the parenting style has the potential to mitigate the severity of callous-unemotional traits in adolescents with conduct disorder by influencing personality traits. The intensity of these traits can be reduced through the implementation of positive parenting methods, as evidenced by the understanding of the effective factors in callous-unemotionalbehavior.